2016
DOI: 10.1187/cbe.15-08-0170
|View full text |Cite
|
Sign up to set email alerts
|

Colleagues as Change Agents: How Department Networks and Opinion Leaders Influence Teaching at a Single Research University

Abstract: This study investigates colleague–colleague relationships within life sciences departments and how they may promote teaching reform. The authors found that discipline-based education researchers are perceived as promoting changes among colleagues in views about teaching and teaching practices. Other faculty may also be leveraged to support change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 52 publications
1
35
0
3
Order By: Relevance
“…This requires different indicators. For instance, research on social networks can be useful because it helps identify opinion leaders and tracks relationships across a social system, such as a department (e.g., Andrews, Conaway, Zhao, & Dolan, 2016;Grunspan, Wiggins, & Goodreau, 2014;Hayward & Laursen, 2018;Quardokus & Henderson, 2015). Examples of social network indicators may be increasing the number of opinion leaders, increasing the density of a network, or increasing the strength of relationships related to undergraduate teaching in a department.…”
Section: Indicatorsmentioning
confidence: 99%
“…This requires different indicators. For instance, research on social networks can be useful because it helps identify opinion leaders and tracks relationships across a social system, such as a department (e.g., Andrews, Conaway, Zhao, & Dolan, 2016;Grunspan, Wiggins, & Goodreau, 2014;Hayward & Laursen, 2018;Quardokus & Henderson, 2015). Examples of social network indicators may be increasing the number of opinion leaders, increasing the density of a network, or increasing the strength of relationships related to undergraduate teaching in a department.…”
Section: Indicatorsmentioning
confidence: 99%
“…Auerbach and colleagues [54] used Poisson regression to model the number of times an instructional practice, such as promoting metacognition, was noticed by experts compared to novices as they analyzed videos of active-learning classrooms. Andrews and colleagues [55] by counting the number of times a faculty member was reported in a survey as the cause of a change, thus necessitating a Poisson model of their count data.…”
Section: F Poisson Regression 1 When To Use Poisson Regressionmentioning
confidence: 99%
“…Many studies have relied on co-authorship or citation networks to study faculty social networks, but these networks may not appropriate for studying faculty teaching social networks (Kezar 2014a;Xian and Madhavan 2014). Indeed, Quardokus and Henderson (2015) argued that networks such as departmental affiliation are poor proxies for faculty teaching networks and Andrews et al (2016) show that discipline-based education researchers maintain teaching networks that transcend their individual departments. Although, few studies have examined how the teaching social networks of faculty influence their teaching practices, we describe the few that we know of.…”
Section: Social Network Analysis and Faculty Teaching Practicesmentioning
confidence: 99%
“…Both of these studies suggest that most faculty teaching networks are too sparse to benefit from either strong or bridging network ties. Andrews et al (2016) found that faculty change their teaching practices in response to colleague-colleague interactions, especially with colleagues deemed as opinion leaders. Opinion leaders were identified as faculty who were seen as excellent teachers or had unique teaching expertise because they conducted discipline-based education research.…”
Section: Social Network Analysis and Faculty Teaching Practicesmentioning
confidence: 99%